2016
DOI: 10.7309/jmtm.5.1.5
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Use and Perceptions among Medical Students and Practicing Physicians

Abstract: Background: Smartphones have become mainstream, including in the healthcare setting. However, little formal research has been performed to examine mobile medical technology.Aims: To examine smartphone use and perceptions among medical students and physicians in a statewide medical university.Methodology: An IRB approved 23-item survey eliciting smartphone use and perceptions was developed by the research team and an e-mail invitation for participation was sent to all medical students, resident and attending ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 15 publications
0
14
0
1
Order By: Relevance
“…With only a small proportion of students not having access to appropriate technology (Buchholz et al, 2016;Gikas & Grant, 2013;Gökçearslan et al, 2016;Ozdalga et al, 2012), it may not be access that prevents student usage, but rather student willingness to register with particular SoMe accounts and then to engage with them for learning. VLEs are considered compulsory resources by institutions and can be accessed through the same devices, so citing technological availability may not be a fair justification for not using SoMe in L&T.…”
Section: Specific Advantages and A Range Of Approaches And Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…With only a small proportion of students not having access to appropriate technology (Buchholz et al, 2016;Gikas & Grant, 2013;Gökçearslan et al, 2016;Ozdalga et al, 2012), it may not be access that prevents student usage, but rather student willingness to register with particular SoMe accounts and then to engage with them for learning. VLEs are considered compulsory resources by institutions and can be accessed through the same devices, so citing technological availability may not be a fair justification for not using SoMe in L&T.…”
Section: Specific Advantages and A Range Of Approaches And Purposesmentioning
confidence: 99%
“…Worldwide, there are more than one billion active users of Facebook (Facebook, 2017) and YouTube (YouTube, 2017), and over 300 million active monthly users of Twitter (Twitter, 2017). These figures include high levels of SoMe activity among undergraduate students for educational as well as social purposes (Ali, 2016;Guraya, 2016;Knight-McCord et al, 2016;Roblyer, McDaniel, Webb, Herman, & Witty, 2010;Tess, 2013) and such usage parallels the availability of remote SoMe access achieved through uptake in smart devices (Buchholz, Perry, Weiss, & Cooley, 2016;Evrim, 2014;Gökçearslan, Mumcu, Haşlaman, & Çevik, 2016;Ozdalga, Ozdalga, & Ahuja, 2012;Ponce, Méndez, & Peñalvo, 2014). In the early to mid2000s, SoMe and Web 2.0 arose as new, exciting and innovative technologies (Boyd & Ellison, 2007) that instructors began to incorporate into educational activities (Booth & Hultén, 2003;Mazer, Murphy, & Simonds, 2007) and the increasing interest in SoMe during this period is reflected in the volume of educational literature on this topic (Asiri & Househ, 2016;Aydin, 2012;Kakushi & Evora, 2016;Lafferty & Manca, 2015;McAndrew & Johnston, 2012;Pander, Pinilla, Dimitriadis, & Fischer, 2014;& Cochran, 2012), blurring of the staff-student boundary (Mazer et al, 2007); unprofessional usage (Kitsis et al, 2016); and impacts on lecturer credibility (Hutchens & Hayes, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Chatterley and Chojecki reported that 35% of students regularly had problems in downloading programs, updating resources, and using wireless Internet and they were frustrated by lack of technical support [ 12 ]. Inexperience and lack of comfort with technology were also described as significant barriers in other studies [ 6 , 25 ]. Safdari et al showed that the technical skills of using medical “apps” of a significant percentage of medical UGs (31%) were only at an elementary level [ 20 ].…”
Section: Discussionmentioning
confidence: 87%
“…As a solution to this significant barrier, initiation of hand-held computer training in the first year of medical school with ongoing training during clinical rotations has been recommended [ 28 ]. Similarly other authors also recommended that mobile medical technology should be integrated at the beginning of UG medical education providing training and encouragement to medical students from the very first year [ 6 , 29 ]. Therefore, institutions could promote PEDs usage by providing training and knowledge to build confidence in technology as a part of curriculum for medical UGs, especially during their early years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation